Development of antimalarial human monoclonal antibodies against Plasmodium falciparum - Wang, LT (2022)
Advances in high-throughput isolation of neutralizing human monoclonal antibodies (mAbs) have enabled development of mAb-based therapeutics for many viruses (e.g., HIV-1, Ebola, SARS-CoV-2). This approach has recently been applied to isolate antimalarial human mAbs against the Plasmodium falciparum circumsporozoite protein (CSP) on sporozoites (SPZ) and reticulocyte-binding protein homolog 5 (RH5) on merozoites (MZ). CSP and RH5 are leading malaria vaccine targets because they are respectively required for the SPZ and MZ stages of malaria parasites to invade host hepatocytes and erythrocytes. CSP has three domains: an N-terminus, a central region composed of repeating NPDP/NVDP/NANP tetrapeptides, and a C-terminus. A truncated form of CSP containing 19 NANP repeats and the C-terminus is the antigenic target of the world’s only approved malaria vaccine (RTS,S). RTS,S formulated with the adjuvant AS01 elicited protective CSP antibodies but was only 30-50% effective at preventing malaria in a phase III trial. The focus of this Thesis is the isolation of potent human mAbs that bind new sites of vulnerability on CSP (and RH5) in order to facilitate clinical development of promising antimalarial mAbs and improve designs of vaccines targeting these antigens.